Device associated infections among neonates in neonatal intensive care units: a single unit survey study in Cairo, Egypt - Ibrahim, Mohamed Farouk M.; Mohamed, Hanem Abdullah; Abdelfattah, May; ElTatawy, Sara S. (International Journal of Contemporary Pediatrics, 2020)
Background: Device Associated Infection (DAI) namely Ventilator Associated Pneumonia (VAP) and Central Line Associated Blood Stream Infection (CLABSI) is one of the challenges for both neonatal nurses and doctors. Aims of the study were 1) Assess the rate of DAI occurrence among neonates, 2) explore the relationship between DAI rates and certain risk factors such as nurse patient ratio, hand hygiene practice, gestational age (GA), weight, and length of hospital stay among neonates. Methods: Descriptive correlational survey research design. Sample: All neonates admitted in twelve months-duration were included (total number 1090 neonates). Nurses and doctors were observed for compliance to adequate hand hygiene technique. Tools: 1) Center for Disease Control (CDC) criteria to calculate DAI rates, 2) Hand hygiene five points checklist 3) Review of neonates charts to collect data as weight, GA 4) Ballard score and 5) nurse/patient ratio. Results: 24 neonates developed DAI, high significant negative correlations between DAI and infants’ weight, GA, nurse/patient ratio and overall compliance to hand hygiene techniques were reported (p-value ≤0.05). Length of hospital stay, inadequate hand hygiene technique had strong positive correlations with DAI rate (p-value ≤0.05). Conclusions: Factors that could affect DAI were infant’s weight, GA, length of hospital stay, inadequate hand hygiene technique and nurse/patient ratio. Recommendations: implementation of infection control programs to raise nurses as well as physicians’ compliance to adequate hand hygiene technique and increase number of nurses in the Neonatal Intensive Care Unit (NICU) per shift.